Influence Of Impurity Ni Atoms on The Electrophysical Parameters of Si - N.A.Turgunov; E.Kh.Berkinov; R.M.Turmanova; N.B.Xaytimmetov; L.E.Madaliyev (Genius Journals, 2023)
Currently, silicon single crystals doped with impurity atoms of 3d transition metals forming bulk impurity nozzles in silicon are considered widely studied materials in terms of obtaining semiconductor materials with predetermined parameters, as well as control of electrophysical parameters
Keywords: electrophysical; parameters; obtaining